From Nollywood to New Media: The Transformation of Cultural Narratives in Nigeria’s Digital Communication Landscape - Kenneth Uyi Abudu; Fadhilatul Khaira; Mohammad Raudy Gathmyr (MD Research Center, 2026)
The digital transformation of Nigeria’s Nollywood industry reflects significant changes in how cultural narratives are produced, distributed, and interpreted, yet existing scholarship has largely failed to provide a comprehensive analysis of how digital media reshapes cultural narratives, power relations, and identity in the Nigerian context. This study aims to analyze how digital media reshapes cultural narratives as well as power relations and identity within Nigerian society. Employing a qualitative thematic literature review, the study synthesizes scholarly works, reports, and digital campaigns related to cultural narratives in Nigeria’s digital landscape. Theoretically, this study adopts Stuart Hall’s encoding/decoding framework (1980; 1990) to explain that meaning is not fixed but actively negotiated between producers and audiences within diverse socio-cultural contexts. Three main findings emerge. First, Nollywood’s digital transformation occurs through processes of adaptation, resistance, and reinterpretation of local values. Second, digitalization expands the space for expression and global distribution while reinforcing digital inequalities and the dominance of global platforms. Third, digital cultural narratives become dynamic arenas of meaning contestation, where local values interact with global influences through encoding and decoding practices. The study concludes that the integration of technology, digital literacy, and local values is key to building an inclusive and sustainable digital cultural ecosystem in Nigeria, with implications for policymakers, cultural practitioners, and platform developers.